Antimycotic susceptibility testing of dermatophytes in microcultures with a standardized fragmented mycelial inoculum. - Granade, T C (1980)
Standardization of a fragmented dermatophyte mycelial inoculum free of conidia for use in a broth microculture antimycotic susceptibility testing system is described. Ten clinical dermatophyte isolates were grown in submerged broth cultures at 35 degrees C. The mycelia were harvested before conidia appeared and were fragmented to 10 to 50-micron segments with a Broeck ground-glass tissue grinder. The density of the fragmented mycelium preparation was found to be adjustable on the basis of its spectrophotometric density expressed as absorbance measured at 450 nm. The minimal absorbance density that produced a 100% inoculation efficiency was determined for each isolate, and from these data an absorbance density of 0.600 was selected for inoculation of microcultures used in antimycotic susceptibility testing. The 0.600-absorbance inoculum of each dermatophyte isolate was tested for its capacity to successfully inoculate antimycotic agent-containing microcultures and generate minimal inhibitory concentrations of griseofulvin, clotrimazole, miconazole, and ketoconazole. The effect of the length of incubation on the minimal inhibitory concentrations was determined. It was concluded that the 0.600-absorbance density fragmented mycelial inoculum assured the rapid and uniform inoculation of the broth microculture antimycotic susceptibility system.